Differences in lower extremity joint kinematics and kinetics during vertical jumps with and without a lacrosse stick - Sanomura, M.; Sakaguchi, M.; Saho, Y.; Fukubayashi, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Non-contact anterior cruciate ligament (ACL) injury has been reported to occur during the early stance phase of landing and/or cutting (Krosshaug et al., 2007). The incidence rate of ACL injury in women lacrosse athletes is higher than those in other competitive athletes. The purpose of this study was to compare lower extremity joint kinematics and kinetics during drop vertical jumps with and without a lacrosse stick. Methods Nine female collegiate lacrosse players participated in our study (mean age, 20.0 ± 1.3 years; height, 159.6 ± 5.8 cm; weight, 55.1 ± 6.3 kg; lacrosse experience, 24 ± 3.4 months). An 8-camera motion analysis system and a force plate were used to record three-dimensional marker positions and ground reaction forces, sampled at 240 Hz and 2400 Hz, respectively. The subjects were asked to perform the double-leg drop vertical jump from a 30-cm-high box (landing on a force plate with their right foot), and raising both arms above the head when vertical jumping, and were recorded for each of the 3 conditions; not holding a lacrosse stick (NH); holding a lacrosse stick in the right hand (RH); and holding a lacrosse stick in the right hand with a target ball (RHT). The values of knee abduction and hip adduction, knee and hip flexion angles at initial foot contact, and the peak values of knee abduction and hip adduction, knee and hip flexion angles, and peak knee abduction and hip adduction moments during the first 30% of the landing phase were compared among the 3 conditions. Results The peak knee flexion angle in the RHT trial was significantly smaller than that in the RH trial during the first 30% of the landing phase (109.7 ± 10.4° vs. 113.5 ± 9.8°, p < 0.05). No significant differences in any other parameters were observed. Discussion The extended knee position during the landing from a jump has been reported may be a risk factor for ACL injury, as assessed by video analysis of actual injury and laboratory motion analysis (Renstrom et al., 2008). With respect to the relationship between the sagittal plane of the knee flexion angle and ACL strain, a cadaveric study showed that quadriceps muscle contraction at a smaller knee flexion angle produces an anterior shear force on the tibia relative to the femur (Li et al., 1999). The results of this study suggest that the RHT trial tended to have a smaller knee flexion angle during landing than the RH trial. Therefore, the drop jump task holding a lacrosse stick with a target (e.g., a lacrosse ball) may be useful as a screening test to prevent lower extremity injuries, such as ACL injury, in female lacrosse athletes.